Self-reported impulsivity in women with borderline personality disorder: the role of childhood maltreatment severity and emotion regulation difficulties - Krause-Utz, Annegret; Cackowski, Sylvia; Paret, Christian; Ende, Gabriele; Elzinga, Bernet (BioMed Central, 2019)
Background: Childhood maltreatment, such as severe emotional, physical, and sexual abuse and neglect, has been linked to impulse control problems and dysfunctional emotional coping. In borderline personality disorder (BPD), a history of childhood maltreatment may worsen difficulties in emotion regulation, which may in turn give rise to impulsive behaviours. The aim of this self-report study was to investigate associations between childhood maltreatment severity, emotion regulation difficulties, and impulsivity in women with BPD compared to healthy and clinical controls. Methods: Sixty-one female patients with BPD, 57 clinical controls (CC, women with Attention Deficit Hyperactivity Disorder and/or Substance Use Disorder, without BPD), and 60 female healthy controls (HC) completed self-report scales on childhood trauma (Childhood Trauma Questionnaire, CTQ), difficulties in emotion regulation (Difficulties in Emotion Regulation Scale, DERS), and impulsivity (UPPS Impulsive Behaviour Scale). A conditional process analysis was performed to investigate whether emotion dysregulation statistically mediated the effect of childhood maltreatment severity on impulsivity depending on group (BPD vs. CC vs. HC). Results: Childhood maltreatment, particularly emotional maltreatment, was positively associated with impulsivity and emotion regulation difficulties across all groups. Difficulties in emotion regulation statistically mediated the effect of childhood maltreatment on impulsivity in BPD, but not in the other groups. Conclusion: In the context of current conceptualizations of BPD and previous research, findings suggest that problems with emotion regulation may be related to a history of childhood maltreatment, which may in turn enhance impulsivity. Targeting emotion dysregulation in psychotherapy and discussing it in relation to childhood maltreatment can help decreasing impulsive behaviors in individuals with BPD. Given the correlational design of our study which does not allow causal conclusions, future studies have to employ prospective, experimental designs and include larger sample sizes to corroborate associations between childhood maltreatment, emotion dysregulation, and impulsivity.
In: Borderline Personality Disorder and Emotion Dysregulation, 6 (2019), Nr. 6. pp. 1-14. ISSN 2051-6673
Gesehen am 16.05.2019